Rencana Strategik dalam Rangka Menghadapi Persaingan di RSU Siti Asiyah Bumiayu - Filliana Savitri; Erliany Syaodih; Dadang Kusnad (Masyarakat Ekonomi Syariah Bogor, 2026)
This research aims to formulate a strategic plan for Siti Asiyah Bumiayu Hospital in facing the increasingly competitive competition of the health service industry in the Bumiayu District area. The research method used is qualitative with a case study approach, where data is collected through in-depth interviews with management and analysis of organizational strategic plan documents. Data analysis was carried out using the Internal Factor Analysis Strategy (IFAS), External Factor Analysis Strategy (EFAS), and TOWS matrix to map the competitive position of hospitals. The results of the study showed that RSU Siti Asiyah Bumiayu was in Quadrant III (Defensive/Survival) with a coordinate point (-0.20; -0.13), which indicated that the organization had significant internal weaknesses, such as the stigma of old buildings and the limited number of specialist doctors, amid a major threat from modern competitors around it. The recommended priority strategies are the WT (Weakness-Threats) strategy which focuses on risk mitigation through the gradual physical renovation of buildings, recruitment of specialist doctors, optimization of digital marketing to improve the image of hospitals, and the development of superior service units to prepare for the transition to a sustainable classification of type C hospitals.